The Evolution of the NATO-Russia Relations - V. I. Batyuk (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Over the past 30 years, NATO-Russia relations have come a long way. The present paper provides a retrospective analysis of the NATO-Russia relations that may shed new light on their current state and prospects for development. The author shows that after the collapse of the bipolar world, and the Russian Federation’s emergence on the international scene as a sovereign state, Moscow did not exclude the possibility of establishing partnership and even allied relations with the North Atlantic Alliance. In fact, during the 1990s2000s, Russia and the Alliance cooperated successfully in such areas as the ﬁght against piracy and international terrorism, rescue at sea, etc. However, hopes for a full-ﬂedged partnership between Moscow and Brussels did not materialize as a result of the Alliance’s advance to the East, to the Russian border. NATO’s eastward enlargement — combined with the ﬁrm position of the oﬃcial Washington and Brussels on the unacceptability of Russia’s membership in the Alliance — meant a complete exclusion of Russia from the decision-making process on the European security. At the same time, for a variety of reasons, in the post-bipolar world the military-political dependence of the Western European subregion on Washington did not decrease, as many hoped, but, on the contrary, has increased, thus excluding for Moscow the very possibility to play on the contradictions between the United States and its European allies. Accession to the Alliance of the Eastern and Southern European ‘recruits’ (many of which shared strong anti-Russian sentiments) further limited the Russia’s possibilities for such maneuvering. The Alliance thus became an instrument of the US global domination — a domination which Moscow rejects categorically. The author concludes that in these circumstances, it will not be easy to overcome the military-political contradictions between Russia and NATO.